Evaluation of Recombinant Interleukin-2 on Humoral Immune Response of Newcastle Disease Vaccinated Chickens - R.D. Padalkar, B.E. Shambulingappa* and (Journal of Experimental Sciences, 2011)
Totally 120 chickens belonging to three groups (group-A, B and C) were used to study the effect of Rec IL-2 on specific immunity of Newcastle disease vaccinated chickens. Serum samples collected at 6th,12th and 18th days post vaccination (F strain and R2B strain) were subjected to HI test and SRID test to assess the specific immunity of chickens.HI test results of chickens vaccinated with R2B strain of NDV revealed the titre values in group-A showing 1:256,1:256 and 1:512 in the samples collected at 6th ,12th and 18th days of post vaccination respectively. Whereas titre values in group-B were also in increasing trend, but remained at 1:256 titres. Group-C showed minimal titre values at 18th days of post vaccination (1:4).SRID test results revealed the readings of antibodies levels in group-A after vaccination with R2B strain, raised up to 4 mg/ml in 18th day sampling, while group-C showed 2.5 mg/ml of antibodies even in 18th day of sample collection indicating immunomodulatory effect of Rec IL-2 in vaccinated chickens.